Real wages and labour productivity in Britain and Germany, 1871-1938: a unified approach to the international comparison of living standards - Stephen Broadberry; Carsten Burhop (Max Planck Institute for Research on Collective Goods, 2009)
Throughout the period 1871-1938, the average British worker was better off than the average German worker, but there were significant differences between major sectors. For the aggregate economy, the real wage gap was about the same as the labour productivity gap, but again there were important sectoral differences. Compared to their productivity, German industrial workers were poorly paid, whereas German agricultural and service sector employees were overpaid. This affected the competitiveness of the two countries in these sectors. There were also impor-tant differences in comparative real wages by skill level, affecting the extent of poverty.
Keywords: N13; N33; E24; 330; Economic history; Britain; Germany; Real wages; Reallohn; Arbeitsproduktivität; Qualifikation; Verarbeitendes Gewerbe; Dienstleistungssektor; Komparativer Kostenvorteil; Internationaler Wettbewerb; Vergleich; Großbritannien; Deutschland (bis 1945)